TINGKAT KEMATANGAN ( MATURITY LEVEL ) TATA LAKSANA INFORMASI MENGGUNAKAN COBIT 5 PADA MANAJEMEN PROGRAM DAN PROYEK : STUDI KASUS PT. XYZ - Triyanto, Toeko; Gata, Windu (Jurnal Gerbang STMIK Bani Saleh, 2018)
PT XYZ is established in 2013. The company is already using information technology and has the IT division with the program and information systems used by the company is the inhouse production of the IT division. Along with business development company then many changes also in the information system used, it brought a lot of development projects and the addition of the system carried out by the IT division. In this case the project is fully regulated by the IT division began the initial stage to implementation and is delivered to the user. Currently, there has never been an evaluation for project management carried out by IT. therefore it is necessary to evaluate the specific standardization, here the author uses COBIT 5 framework that focuses on the process BAI01 that manage program and project. To determine the selected responder is using RACI Chart for later than the specified responder responder list that will fill out a questionnaire with purposive sampling method. Making a questionnaire based on practical guidance BAI01 COBIT 5 process by using a scale of measurement methods guffman. From the evaluation of PT Morinaga Kino Indonesia has capabliity BAI process level at 3.04 with a target level of 4 so had a gap of 0.96 with a breakdown per sub process that is BAI01.01 = 2.50, BAI01.02 = 2.60, BAI01 .03 = 3.05, BAI01.04 = 2.91, BAI01.05 = 3.40, BAI01.06 = 2.28, BAI01.07 = 4.67, BAI01.08 = 1.93, BAI01.09 = 3.05, BAI01.10 = 3.17, BAI01.11 = 2.90, BAI01.12 = 3.37, BAI01.13 = 3.72,BAI01.14 = 3.07. things that need to be improved is planning a project that has a capability level of 1.93.